2006
DOI: 10.14214/sf.326
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite variation of Quercus aquifolioides populations at varying altitudes in the Wolong Natural Reserve of China

Abstract: Genetic variation and differentiation were investigated among five natural populations of Quercus aquifolioides occurring along an altitudinal gradient that varied from 2000 to 3600 m above sea level in the Wolong Natural Reserve of China, by analyzing variation at six microsatellite loci. The results showed that the populations were characterized by relatively high intra-population variation with the average number of alleles equaling 11.33 per locus and the average expected heterozygosity (H E ) being 0.779.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
3
10
0
1
Order By: Relevance
“…This would be the case in our study for the potential outlier loci, which without being adaptive markers, could be used for the identification of selection effects. Similar selection effects have been reported in genetic studies of different oak species by using nuclear microsatellites (Neophytou et al, 2010;Ramirez-Valiente et al, 2010;Zhang et al, 2006). Further, large changes in allele frequencies at eight microsatellite loci observed in Drosophila populations indicated selectively-driven changes and provided evidence about genomewide selective sweeps that affect not only fitness but also linked neutral loci (Montgomery et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…This would be the case in our study for the potential outlier loci, which without being adaptive markers, could be used for the identification of selection effects. Similar selection effects have been reported in genetic studies of different oak species by using nuclear microsatellites (Neophytou et al, 2010;Ramirez-Valiente et al, 2010;Zhang et al, 2006). Further, large changes in allele frequencies at eight microsatellite loci observed in Drosophila populations indicated selectively-driven changes and provided evidence about genomewide selective sweeps that affect not only fitness but also linked neutral loci (Montgomery et al, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…We found that the medium-altitude population had the highest genetic diversity; a similar result was obtained for Quercus aquifolioides in Wolong Nature Reserve (Zhang, 2006). The high genetic diversity observed in the medium-altitude population may be attributable to the better habitat there.…”
Section: Discussionsupporting
confidence: 83%
“…The genetic differentiation of populations at different altitudes has been detected in some species (Bellusci et al, 2005;Zhang, 2006); however, some studies have reported little or no genetic variation between populations at different altitudes (Aradhya et al, 1993;Oyama et al, 1993;Gehring and Delph, 1999). In this study, SSR markers, combined with population genetic theory, were used to study the genetic diversity and population genetic structure of C. eyrei with changing altitude.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al, 2008), while only little or no differences with respect to altitude have also been reported (e.g. Zhang et al, 2006;see also, Ohsawa & Ide, 2008). Effective dispersal is a key factor that prevents the development of altitudinal structuring in genetic variation patterns.…”
mentioning
confidence: 96%